Normative and Legal Asрects of a Tourist Activity in Ukraine - Yullia Savchuk; Yuliia Maslova (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2019)
The article outlines the general principles of legal regulation of tourist and tourist agency activities. The main differences between the tourist operator and the travel agent in accordance with the Law of Ukraine «On Tourism» are investigated.